Involving an individual with lived‐experience in a co‐analysis of qualitative data. (31st March 2021) - Hemming, Laura; Pratt, Daniel; Bhatti, Peer; Shaw, Jennifer; Haddock, Gillian
Abstract: Background: People with lived‐experience of the phenomenon under investigation are seldom involved in the analysis of qualitative data, and there exists little guidance for those wishing to involve contributors at this stage of research. Aims: To critically reflect on the process of involving people with lived‐experience in a thematic analysis and to offer direction to other researchers. Methods: An individual with lived‐experience of residing in prison contributed to a co‐analysis of qualitative data using thematic analysis. This paper reports on involvement at each stage of a thematic analysis and follows an established reporting checklist. Results: A number of challenges and benefits were encountered in the process of co‐analysing the data. These are discussed in relation to previous research and how to overcome the challenges encountered. Conclusions: The paper concludes by giving recommendations and guidance for future researchers wishing to involve people with lived‐experience in qualitative data analysis.